2020
DOI: 10.1186/s12199-020-00912-2
|View full text |Cite
|
Sign up to set email alerts
|

Acute effect of ambient fine particulate matter on heart rate variability: an updated systematic review and meta-analysis of panel studies

Abstract: Background Decreased heart rate variability (HRV) is a predictor of autonomic system dysfunction, and is considered as a potential mechanism of increased risk of cardiovascular disease (CVD) induced by exposure to particulate matter less than 2.5 μm in diameter (PM2.5). Previous studies have suggested that exposure to PM2.5 may lead to decreased HRV levels, but the results remain inconsistent. Methods An updated systematic review and meta-analysis of panel studies till November 1, 2019 was conducted to evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 60 publications
0
13
0
Order By: Relevance
“…and Europe showed that a 0.92% reduction in SDNN was observed for a 10 μg/m 3 increase in short-term PM 2.5 exposure [49]. Wang et al showed that 0.39% (95% CI: -0.72%, -0.06%) and 0.92% (95% CI: -2.14%, 0.31%) reductions were observed for short-term and long-term exposures to a 10 μg/m 3 increase in PM 2.5 , respectively, for adults aged above 55 years old [50].…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…and Europe showed that a 0.92% reduction in SDNN was observed for a 10 μg/m 3 increase in short-term PM 2.5 exposure [49]. Wang et al showed that 0.39% (95% CI: -0.72%, -0.06%) and 0.92% (95% CI: -2.14%, 0.31%) reductions were observed for short-term and long-term exposures to a 10 μg/m 3 increase in PM 2.5 , respectively, for adults aged above 55 years old [50].…”
Section: Resultsmentioning
confidence: 98%
“…A signi cant decrease in SDNN (0.51%; 95% CI: 0.01-1.01%) was associated with a 10 µg/m 3 increase in PM 2.5 for Japanese patients aged 20-90 years [48]. A meta-analysis of 33 panel studies in North America, Asia, and Europe showed that a 0.92% reduction in SDNN was observed for a 10 μg/m 3 increase in short-term PM 2.5 exposure [49]. Wang et al showed that 0.39% (95% CI: -0.72%, -0.06%) and 0.92% (95% CI: -2.14%, 0.31%) reductions were observed for short-term and long-term exposures to a 10 μg/m 3 increase in PM 2.5 , respectively, for adults aged above 55 years old [50].…”
Section: Resultsmentioning
confidence: 98%
“…A significant decrease in SDNN (0.51%; 95% CI: 0.01-1.01%) was associated with a 10 µg/m 3 increase in PM 2.5 for Japanese patients aged 20-90 years 58 . A meta-analysis of 33 panel studies in North America, Asia, and Europe showed that a 0.92% reduction in SDNN was observed for a 10 μg/m 3 increase in short-term PM 2.5 exposure 59 . Wang et al showed that 0.39% (95% CI: − 0.72%, − 0.06%) and 0.92% (95% CI: − 2.14%, 0.31%) reductions were observed for short-term and long-term exposures to a 10 μg/m 3 increase in PM 2.5 , respectively, for adults aged above 55 years old 60 .…”
Section: Discussionmentioning
confidence: 99%
“…It should be mentioned that recent studies particularly underline negative impact of ultrafine particles (UFP, diameter below 0.1 µm) in the air on various body organs (see e.g., Bevan et al, 2020;Daiber et al, 2020;Niu et al, 2020;Shkirkova et al, 2020). Unfortunately, continuous field measurements of the UFP level in the air are conducted very rarely.…”
Section: Health Risk Related To Marathon Runningmentioning
confidence: 99%